Bactericidal antibiotics promote reactive oxygen species formation and inflammation in human sinonasal epithelial cells. Issue 2 (1st December 2015) - Kohanski, Michael A.; Tharakan, Anuj; Lane, Andrew P.; Ramanathan, Murugappan
Abstract : Background: Bactericidal antibiotics have been shown to stimulate reactive oxygen species (ROS) formation in mammalian cells through mitochondrial dysfunction. This results in oxidative tissue damage that may have negative consequences for long‐term antibiotic use. Antibiotics are widely and heavily used in the treatment of acute and chronic sinusitis; however, the relationship between antibiotics and ROS formation in sinonasal epithelial cells (SNECs) has not yet been demonstrated. Methods: Human SNECs were collected from patients during endoscopic sinus surgery and grown in culture at the air‐liquid interface. Differentiated SNECs were stimulated with the bactericidal antibiotics amoxicillin and levofloxacin and the bacteriostatic antibiotic clarithromycin for 24 hours. ROS were quantified via fluorescence. Cell death was quantified by lactate dehydrogenase (LDH) secretion. Expression of inflammatory markers such as tumor necrosis factor α (TNF‐α) and nuclear factor erythroid 2–related factor 2 (Nrf2)‐mediated antioxidant genes were measured by real‐time polymerase chain reaction (RT‐PCR). Results: Cultured SNECs treated with the bactericidal antibiotics amoxicillin and levofloxacin resulted in a significant increase in production of ROS ( p < 0.05) and secretion of LDH ( p < 0.05). The increase in ROS formation correlated with an increase in expression of Nrf2‐mediated antioxidant genes as well as the expression and production of proinflammatory cytokine TNF‐α, and interleukin 1 β (IL‐1β) ( p < 0.05). SNECs treated with clarithromycin did not demonstrate statistically significant increases in ROS or proinflammatory cytokine production. Conclusion: In this study, we show that treatment of cultured human SNECs with bactericidal antibiotics leads to formation of ROS with an associated increase in inflammatory and antioxidant gene expression and cell death. This suggests that long‐term or inappropriate antibiotic use in the treatment of sinusitis may result in oxidative tissue damage to the sinonasal epithelium. Future studies will explore the clinical implications of such damage to the sinonasal epithelium.